Penerapan Tata Kelola Lembaga Perkreditan Desa Pada Desa Adat Ketewel Kecamatan Sukawati - Anak Agung Mas Suandari; I Wayan Sudiana (UNHI Press, 2023)
ABSTRACT Corporate Governance is a set of structured processes used to manage and direct or lead a business with the intention of increasing corporate value and business continuity. The purpose of this research is to find out how the principles of corporate governance are applied to the LPD in Ketewel Traditional Village. The method used in this research is descriptive qualitative method. The results of the study show that the implementation of village credit institution governance at the Ketewel Traditional Village LPD has been going quite well, by implementing the five GCG principles, but there are still indicators of GCG principles that have not been maximized, namely the principle of accountability. The Ketewel Traditional Village LPD has not optimally conducted training and seminars for employees, the training and seminars that have been conducted so far are still general and internal in nature. In increasing competitiveness outside with other companies, in the future the Ketewel Traditional Village LPD in training and seminars needs to be held externally so that employees can learn new things and add various insights and knowledge outside the company to enhance the development and progress of the company.